1991
DOI: 10.1093/nar/19.15.4153
|View full text |Cite
|
Sign up to set email alerts
|

A new cAMP response element in the transcribed region of the human c-fos gene

Abstract: In NIH 3T3 cells the c-fos gene is induced rapidly and transiently by cAMP. As shown by the analysis of 3T3 cells stably transfected with promoter mutants of the human c-fos gene this induction does not depend on the dyad symmetry element (position -320 to -300), but involves at least two other non-related sites: an element located around position -60 resembling the cAMP response element of the fibronectin and somatostatin genes (which has been described before), and an element located between positions +18 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…CRE is one of the important cis DNA elements in the c-fos gene promoter. 23 Infection of AdCREBM1 strongly inhibited thrombin-induced c-fos mRNA expression in VSMCs ( Figure 4B). …”
Section: Inhibition Of Thrombin-induced C-fos Mrna Expression By Overmentioning
confidence: 90%
See 1 more Smart Citation
“…CRE is one of the important cis DNA elements in the c-fos gene promoter. 23 Infection of AdCREBM1 strongly inhibited thrombin-induced c-fos mRNA expression in VSMCs ( Figure 4B). …”
Section: Inhibition Of Thrombin-induced C-fos Mrna Expression By Overmentioning
confidence: 90%
“…23 CRE in the promoter region plays a critical role in the induction of c-fos gene expression in response to mitogens. We showed that overexpression of the dominant-negative form of CREB strongly suppressed thrombin-induced c-fos mRNA expression, confirming the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several key differences in the promoters of the two genes as well. The c-fos promoter contains two cyclic adenosine monophosphate (cAMP) binding protein response (CRE)-like elements upstream of the transcription start site (TATA box) that confers enhancement of c-fos expression via cAMP (Hartig et al, 1991). The fra-2 promoter lacks a TATA box and has only one CRE (Yoshida et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, bovine CYPJ7 gene (38) and human c-fos gene (39) have been shown to be tightly regulated by cAMP but consensus CRE sequences have not been found in the 5' regulatory regions of these genes. It is of interest that Godfrey et al (25) reported the presence of an AP-2-like sequence (TGGGGA) in the 5' regulatory region of a MNP gene of P. chrysosporium.…”
Section: Discussionmentioning
confidence: 99%